Spatial patterns of multidrug-resistant tuberculosis: correlation with sociodemographic variables and type of notification - Ingrid Bentes Lima; Laura Maria Vidal Nogueira; Ricardo José de Paula Souza e Guimarães; Ivaneide Leal Ataide Rodrigues; Suzana Rosa André; Paula Daniella de Abreu; Perla Katheleen Valente Corrêa (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Correlate the cases of multidrug-resistant tuberculosis and its spatial patterns with the type of notification and sociodemographic variables. Method: Ecological study carried out in the municipality of Belém, with 77 cases of multidrug-resistant tuberculosis registered in the Special Treatment Information System for Tuberculosis, between 2012 and 2016. For analysis, the data was debugged followed by geo-referencing in ArcGis 10.3 and Terra View 4.2.2. To relate the cases with the type of notification, the BioEstat 5.4 software was used, with a significance level of 95%. Results: Of the total, 40 (52%) were new cases; 27 (35%), relapses; and ten (13%) were re-enrolled after leaving. Multidrug-resistant tuberculosis was randomly distributed and related to income, household, territorial cluster and water supply. There was a concentration of cases in two administrative districts, corresponding to 28.5% and 27.3% of the total, with a median Sociodemographic Index. Conclusion: Behavior of multidrug-resistant tuberculosis influenced by sociodemographic indicators.